The genus Leptoplana (Leptoplanidae, Polycladida) in the Mediterranean basin. Redescription of the species Leptoplana mediterranea (Bock, 1913) comb. nov. - Gammoudi, Mehrez; Egger, Bernhard; Tekaya, Saïda; Noreña, Carolina (Zootaxa, 2012)
A revision of the genus Leptoplana Ehrenberg, 1831 in the Mediterranean basin is undertaken. This revision deals withthe distribution and validity of the species of Leptoplana known for the area. The Mediterranean sub-species polyclad,Leptoplana tremellaris forma mediterranea Bock, 1913 is elevated to the specific level. Leptoplana mediterranea comb.nov. is redescribed from the Lake of Tunis, Tunisia. This flatworm is distinguished from Leptoplana tremellaris mainlyby having a prostatic vesicle provided with a long diverticulum attached ventrally to the seminal vesicle, a genital pit clos-er to the male pore than to the female one and a twelve-eyed hatching juvenile instead of the four-eyed juvenile of L. tremellaris. The direct development in L. mediterranea is described at 15 °C.